2014
DOI: 10.4103/2224-3151.206732
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the implementation of the integrated management of childhood illness (IMCI) at community health centres in West Java province, Indonesia

Abstract: Interventions aiming to create local regulations endorsing IMCI implementation; promoting monitoring and supervision; encouraging on-the-job training for health workers; and strengthening training programmes, counselling and other promotional activities are important for promoting IMCI implementation in West Java province, and are also likely to be useful elsewhere in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
0
16
2
4
Order By: Relevance
“…Despite the significances of training for IMNCI utilization, only 57.8% of nurses in four districts of west Arsi zones had attended IMNCI training, which was less than WHO recommendation which stated that at least 60% of health care workers seeing sick children in the health facilities should trained how to utilize IMNCI guidelines [15]. However, the finding from present study was higher compared to similar study carried out in Indonesia [16]. The difference could be related to trained staff turnover and high cost of training.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Despite the significances of training for IMNCI utilization, only 57.8% of nurses in four districts of west Arsi zones had attended IMNCI training, which was less than WHO recommendation which stated that at least 60% of health care workers seeing sick children in the health facilities should trained how to utilize IMNCI guidelines [15]. However, the finding from present study was higher compared to similar study carried out in Indonesia [16]. The difference could be related to trained staff turnover and high cost of training.…”
Section: Discussioncontrasting
confidence: 93%
“…IMNCI includes both preventive and curative elements that are implemented by families and communities as well as by health facilities. In summary, the IMNCI strategy includes three main components these include: Improving case management skills of healthcare staff, improving the health systems and improving family and community health practices [3,[5][6].…”
Section: Introductionmentioning
confidence: 99%
“…10 Selain itu, penelitian yang dilakukan oleh Pusat Kajian UI menunjukkan hanya 57% puskesmas yang menjangkau ke seluruh balita. 11 Oleh sebab itu, perlu dilakukan evaluasi terkait pelaksanaan MTBS di Puskesmas pada regional timur Indonesia.…”
Section: Pendahuluanunclassified
“…Temuan ini lebih rendah dibanding hasil penelitian Pusat Kajian UI di Provinsi Jawa Barat, yaitu sebesar 57% Puskesmas telah melayani MTBS ke seluruh balita. 11 Salah satu kunci keberhasilan penerapan MTBS adalah kepatuhan petugas dalam melakukan pemeriksaan balita sakit dengan mengikuti standar yang telah ditentukan. Kepatuhan petugas dalam tata laksana MTBS sangat penting, sehingga balita yang sakit tidak hanya didiagnosis menurut keluhan tetapi dapat didiagnosis secara menyeluruh.…”
Section: Pembahasanunclassified
“…23 Further problems identified during implementation of IMCI in some Southeast Asia countries include the nonuniversal application of management strategies to all children, shortage of trained staff and insufficient supply of IMCI drugs and equipment, as well as lack of facilities and infrastructure. 24 Disease-specific guidelines produced by the WHO have also been implemented in some countries in this region. Evaluation performed by the authors in some of these countries has revealed that only some portions of these intervention packages are adhered to.…”
Section: Prehospital Emergency Medical Carementioning
confidence: 99%